Perceptions of Economic Education Students Towards Indonesian Language Courses - Rusli, Sri Mulyani; Putri, Febrina Riska; Elmiati (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
This study aims to examine students’ perceptions of economics education towards Indonesian language courses or the opinions of students, especially students of the 21st generation of economic education study programs. Regarding Indonesian language courses, there are 3 aspects studied in the research, namely, Indonesian language courses, the nature of perceptions Economic education students and motivation, interest and learning skills. This study uses a survey method. Data collection techniques and sources were obtained using google form media with statements strongly agree, agree, disagree, disagree. The results of the research obtained are in the form of student opinions regarding Indonesian language courses in the form of percentages of strongly agree, agree, disagree, disagree which have been disseminated especially in the Economic Education study program 21. The percentages distributed are in the form of statements regarding the discussions that have been made including components, 1). Indonesian language courses, 2) the nature of students’ perceptions of economic education, 3) motivation, interest and learning skills. The first component explains how the character of the Indonesian language course is and examines more deeply the content of the Indonesian language course. The second component explains students’ opinions on how Indonesian courses that students of economic education think that Indonesian language courses are boring subjects in the learning process without knowing that Indonesian language courses can be studied with their own understanding without any other factors. The third component that really needs to be mastered by students because this third component has many important roles in it where motivation is an internal drive to be active in learning, initial interest or willingness to learn and skills that must be mastered in every learning process.